From hearts to treasury: A systematic review of tax morale's impact on revenue collection - Wijaya, Alif Sukhairi; Irawan, Ferry (Educoretax, 2025)
This research aims to analyze the relationship between tax morale and tax revenue based on a systematic literature review. Tax morale, as the intrinsic motivation of taxpayers to pay taxes, has become a major focus in efforts to improve tax compliance and tax revenue. Through the Systematic Literature Review (SLR) method, this study examines 57 scientific articles published in Scopus and Web of Science indexed journals during the 2010-2024 period. The analysis results show that there is a positive and significant relationship between tax morale and tax revenue. Factors influencing tax morale include trust in government institutions, perceptions of tax system fairness, social norms, and demographic characteristics of taxpayers. Additionally, it was found that policy interventions focusing on improving tax morale are more effective in increasing tax revenue compared to traditional deterrence approaches. This research provides theoretical and practical implications for developing more effective tax policies by considering the psychological and social aspects of taxpayers.